Analytical and experimental research on stability of large slenderness ratio horizontal hydraulic hoist. (October 2018) - Zhou, Ji; Shi, Duan-Wei; Sun, Zhi-Lin; Bi, Tao; Cheng, Xiong-Hao; Chen, Dong; Lu, Yang
Taking the hydraulic cylinder for the miter gate in Dateng Gorges Water Conservancy Project as the object, a large slenderness ratio test hydraulic cylinder was designed based on the similarity theory. The buckling analysis of the test hydraulic cylinder was carried out by the finite element method, considering the friction at the supports, the misalignments between piston rod and cylinder tube, and gravity. The results indicate that the stability safety factor is 10.55. A buckling experimental system was established, and the buckling stability of the test hydraulic cylinder was tested for the sliding bearing support and the rolling bearing support at the piston-rod end, respectively. The stability safety factor is over 9.01 and 6.82 relevantly. The similarities and differences among the results of the finite element method, experimental method, NB/T 35020-2013, and two-sections pressure bar method were analyzed. Experimental and analytical results clearly show that the friction at the supports is a key factor in determining the magnitude of the stability safety for large slenderness ratio horizontal hydraulic hoist and utilizing the sliding bearing can effectively improve the stability safety factor.